«MOSCOW AS AN EMPIRE WILL BE DESTROYED ONLY BY INDEPENDENT NATION-STATES»: THE POSITION OF THE OUN (R) REGARDING THE FUTURE OF THE USSR BEFORE AND DURING THE SOVIET-GERMAN WAR - STETSYSHYN, Oleh (HUMANITARIAN STUDIES: HISTORY AND PEDAGOGY, 2023)
Abstract. The article analyses the position of the Organization of Ukrainian Nationalists (Revolutionary) regarding the future of the Soviet Union, the attitude of S. Bandera's supporters to the national liberation struggle of the nations enslaved by the Kremlin, and their assessment of the decisive role of Ukraine and Ukrainians in these processes. Emphasis is placed on the awareness of the Ukrainians of the fact that in the event of the appearance of independent states of other nations on the territory of Muscovy, the Russian imperial entity will stop to exist. Therefore, the Organization saw its task in the disintegration of Muscovy into separate countries and the creation of a commonwealth of independent national states in place of the empire. The preparation of the OUN (r) for the beginning of the expected national revolutions in the USSR, the collapse of the Red Army and the formation of national liberation environments of the peoples who were under the power of the Kremlin is considered. The readiness of the Organization of Ukrainian Nationalists to cooperate as closely as possible with the enslaved nations is emphasized, that was reflected in the development by the Ukrainian nationalist leadership of the active OUN of instructions on how exactly to act with representatives of these peoples during their joint struggle with Ukrainian nationalists against the Stalinist and Hitler regimes , and also after these national revolutionaries want to return to their native land. The unchanged position of the views of the Organization of Ukrainian Nationalists (Revolutionary) regarding the future state structure of the Russian people as a non-imperial national Russian entity within its ethnographic boundaries is observed.